Was this feedback useful? Examining the observation and feedback process for pre-service teachers. Issue 2 (2nd April 2020) - Rodriguez, Jacqueline; McKinney, Tracy; Powell, Selma; Walker, Zachary; Vince Garland, Krista
ABSTRACT: In many teacher preparation programs at institutions of higher education in the United States, pre-service teachers receive mentoring and constructive feedback during their internship placement from an experienced supervising teacher and a university coordinator. Often the feedback loop is closed by asking interns, 'was this useful?' To better answer this question, researchers employed a phenomenological approach to collect interview and focus group data on the lived experiences, perceptions, and understandings of six pre-service special education interns during their internship experience. Emerging themes included satisfaction with level of support provided by supervisory stakeholders, a feeling of isolation from peer support, special consideration of the components within the evaluation tool, and a request to be provided with additional background information for their assigned university coordinators. These lessons were aggregated, presented, and then integrated into the experiences provided to forthcoming pre-service educators.